1994
DOI: 10.1111/j.1432-1033.1994.tb18587.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic resolution of the reaction catalysed by proton‐translocating transhydrogenase from Escherichia coli as revealed by experiments with analogues of the nucleotide substrates

Abstract: The mechanism, by which transhydrogenase couples transfer of H-equivalents between NAD(H) and NADP(H) to the translocation of protons across a membrane, has been investigated in the solubilised, purified enzyme from Escherichiu coli using analogues of the nucleotide substrates. The key observation was that, at low pH and ionic strength, solubilised transhydrogenase catalysed the very rapid reduction of acetylpyridine adenine dinucleotide (an analogue of NAD+) by NADH, but only in the presence of either NADP' o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 39 publications
8
80
2
Order By: Relevance
“…Previous experiments established that nucleotide binding to domain I is also pH independent [11], and is therefore unlikely to be coupled to proton pumping. In fact, it is becoming increasingly likely that the proton-translocation reactions of transhydrogenase are centred on the NADP ϩ /NADPH binding/release reactions of domain III [1,28,29]. As emphasised above, the release of product NADP ϩ from domain III is extremely slow in the absence of domain II, and this suggests that, in the complete enzyme, an interaction between domain II and the two peripheral domains is responsible for accelerating the release of the nucleotide, and therefore the steady-state rate of transhydrogenation [9].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments established that nucleotide binding to domain I is also pH independent [11], and is therefore unlikely to be coupled to proton pumping. In fact, it is becoming increasingly likely that the proton-translocation reactions of transhydrogenase are centred on the NADP ϩ /NADPH binding/release reactions of domain III [1,28,29]. As emphasised above, the release of product NADP ϩ from domain III is extremely slow in the absence of domain II, and this suggests that, in the complete enzyme, an interaction between domain II and the two peripheral domains is responsible for accelerating the release of the nucleotide, and therefore the steady-state rate of transhydrogenation [9].…”
Section: Discussionmentioning
confidence: 99%
“…X-ray structures reveal nucleotidebinding conformations in which the block may be achieved; essentially the nicotinamide and dihydronicotinamide rings are held apart by the enzyme [24]. The pH dependences of transhydrogenation reactions in bacterial membranes suggest that protonation of the enzyme converts open dIII into its occluded state and, subsequent to the hydride transfer step, deprotonation then converts occluded dIII back into its open state [51,54,55]. Thus, the basic mechanism is (i) substrate nucleotides, NADP + and NADH, associate with their binding sites in an enzyme protomer having both dIII and dI in open states, (ii) protonation of dII from the outside aqueous phase converts the open dIII to occluded, (iii) hydride-ion equivalents are transferred from bound NADH to NADP + , (iv) deprotonation of dII on the cytoplasmic side regenerates the open state of dIII, and (v) the nucleotide products, NADPH and NAD + , are released.…”
Section: The Binding-change Mechanism Of Coupling To Proton Translocamentioning
confidence: 99%
“…This takes place with the dIII component in an ''occluded state'' in which both the binding and release of NADP + and NADPH are extremely slow relative to enzyme turnover [51][52][53]. Crystal structures show that with dIII in the occluded state the pro-R hydrogen atom on C4 of the dihydronicotinamide ring of NADH (on dI) can be brought into close apposition with the si face of C4 of the nicotinamide ring of NADP + (on dIII) to effect direct, stereo-specific and rapid hydride transfer [21].…”
Section: The Binding-change Mechanism Of Coupling To Proton Translocamentioning
confidence: 99%
“…We have described a detailed study of the cyclic reduction of AcPdAD' by NADH in the presence of either NADP' or NADPH by the complete detergent-dispersed transhydrogenase purified from E. coli [20,211. The reaction was very fast (approximately 50 times the rate of the simple reverse reaction at pH 6.0) and depended crucially on the tight binding of NADP' or NADPH to the enzyme.…”
Section: Optical Properties Of the Domain 111 Proteinmentioning
confidence: 99%
“…It proceeds through the reduction of NADP' by NADH, and the subsequent re-oxidation of NADPH by AcPdAD', while NADP'NADPH remain bound to the enzyme [20,211. It was shown from the analysis of the pH dependences of transhydrogenation reactions of the detergentsolubilized E. coli enzyme that the release of NADP' and NADPH are accompanied by the release of a proton [20, 211. There is good reason to believe that the protolytic reactions accompanying the binding and release of the NADP(H) are components of hydrogen ion translocation in the membrane-bound enzyme, and this has provided the basis for a working model to explain the proton-pumping action of transhydrogenase [20,21 1. For the E. coli enzyme at low pH, it was argued that the rates of simple forward (reduction of thio-NADP' by NADH) and reverse (reduction of AcPdAD' by NADPH) transhydrogenation are limited by release from the enzyme of thio-NADPH and NADP', respectively [20,211. The cyclic reaction, however, relies on the presence of tightly bound NADP(H); deuterium isotope measurements showed that its rate is limited by the H--transfer steps.…”
mentioning
confidence: 99%